Immune Profiling of Parkinson’s Disease Revealed Its Association With a Subset of Infiltrating Cells and Signature Genes - Zhang, Xi; Shao, Zhihua; Xu, Sutong; Liu, Qiulu; Liu, Chenming; Luo, Yuping; Jin, Lingjing; Li, Siguang (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is an age-related and second most common neurodegenerative disorder. In recent years, increasing evidence revealed that peripheral immune cells might be able to infiltrate into brain tissues, which could arouse neuroinflammation and aggravate neurodegeneration. This study aimed to illuminate the landscape of peripheral immune cells and signature genes associated with immune infiltration in PD. Several transcriptomic datasets of substantia nigra from the Gene Expression Omnibus database were separately collected as training cohort, testing cohort and external validation cohort. The immunoscore of each sample calculated by single sample gene set enrichment analysis was used to reflect the peripheral immune cell infiltration and to identify the differential immune cell types between PD and healthy participants. According to receiver operating characteristic curve analysis, the immunoscore achieved an overall accuracy of area under curve (AUC) = 0.907 and 0.883 in the training cohort and the testing cohort, respectively. The immunoscore displayed good performance in the external validation cohort with AUC of 0.745. The correlation analysis and logistic regression analysis were used to analyze the correlation between immune cells and PD, and mast cell was identified most associated with the occurrence of PD. Weighted gene co-expression network analysis was used to selected module genes related to mast cell. Least absolute shrinkage and selection operator analysis and random-forest analysis were used to analyze module genes, and two hub genes RBM3 and AGTR1 were identified associated with mast cell in the training cohort. The expression levels of RBM3 and AGTR1 in these three cohorts and cell culture model in vitro revealed that these hub genes were significantly downregulated in PD. In conclusion, this study not only exhibited a landscape of immune infiltrating patterns in PD, but also identified mast cell and two hub genes associated with the occurrence of PD, which provided potential therapeutic targets for PD patients.